Pemberdayaan kader posyandu dalam penyusunan menu ibu hamil dan menyusui untuk pencegahan stunting - Fitriyaningsih, Eva; Rachmawati, Rachmawati; Mulyani, Nunung Sri; Halimatussakdiah, Halimatussakdiah; Lajuna, Lia; Wagustina, Silvia; Al Rahmad, Agus Hendra (Jurnal PADE: Pengabdian & Edukasi, 2025)
The target community of posyandu is in accordance with the target of specific nutrition interventions for handling stunting. Posyandu is a place for pregnant, lactating mothers, infants and toddlers to get services that include maternal and child health in the form of growth and development monitoring, provision of vitamin A capsules, immunization, prevention and control of diarrhea, nutritional counseling according to their problems and family planning. Posyandu cadres are the main drivers of all activities carried out in the posyandu. One of the most basic posyandu problems is the low level of knowledge of cadres both from an academic and technical perspective, therefore to be able to provide optimal services at Posyandu, it is necessary to adjust the knowledge and skills of cadres, so that they are able to carry out Posyandu activities according to the norms, standards, procedures and criteria for developing Posyandu.In preventing stunting, the thing that must be considered is the balanced nutrition of pregnant women and nursing mothers. The purpose of this community service in general is to empower cadres to increase knowledge and skills in compiling and processing menus for pregnant women and nursing mothers as an effort to prevent stunting. The benefits of this activity are to increase the knowledge and skills of cadres in processing a balanced menu for pregnant women and nursing mothers so that cadres can provide this nutrition education widely, sustainably, and independently.Evaluation results showed a significant improvement in cadres' knowledge and skills, as evidenced by the comparison of pre-test and post-test results. A total of 85% of cadres showed a better understanding of nutrition and were able to develop a balanced menu.